Thermodynamic analysis of methane dry reforming - Ying, Kong Zi (2013)
It is well known that methane (a natural gas that is abundantly available) can be reacted with carbon dioxide to produce synthesis gas (a mixture of hydrogen gas and carbon monoxide). Syngas may be converted to gasoline-grade fuels via Fischer-Tropsch synthesis since the petrochemicals in the world was becoming lesser and lesser. In lieu of the significance of the said reaction, the objective for the current work is to study the thermodynamic aspect of methane dry reforming at reforming temperature from 500 to 1000K at atmospheric pressure and different methane to carbon dioxide ratios. The method used in this research is Gibbs free energy minimization. Computation results showed that the temperature affected the product distribution. At low temperature (500K), thermodynamic consideration alone indicated that the methane dry reforming reaction is almost non-existent. Different CO2/CH4 ratios decrease the temperature at which the onset of carbon deposition occurs. Carbon forms at lower temperature and high reactant ratio. At temperature 1000K and CO2:CH4 ratio of 3, the carbon formation value is 1.7.